Determination of Strong Acidic Drugs in Biological Matrices: A Review of Separation Methods. (29th September 2014) - Mu, Lingli; Xie, Feifan; Li, Sanwang; Yu, Peng
Abstract : Strong acidic drugs are a class of chemical compounds that normally have high hydrophilicity and large negative charges, such as organophosphatic compounds and organosulphonic compounds. This review focuses on sample preparation and separation methods for this group of compounds in biological matrices in recent years. A wide range of separation techniques, especially chromatographic method, are presented and critically discussed, which include liquid chromatography (e.g., ion-pair and ion-exchange chromatography), capillary electrophoresis (CE), and other types. Due to the extremely low concentration level of target analytes as well as the complexity of biological matrices, sample pretreatment methods, such as dilute and shoot methods, protein precipitation (PP), liquid-liquid extraction (LLE), solid-phase extraction (SPE), degradation, and derivatization strategy, also play important roles for the development of successful analytical methods and thus are also discussed.